Rural–Urban Educational Inequality in Cambodia: Challenges for Equitable Learning Access - L.Y. Aminas; Mohd Zain Musa (Buletin Edukasi Indonesia, 2026)
Educational inequality between rural and urban communities remains a significant challenge in Cambodia despite ongoing educational reforms and infrastructure development initiatives. Urban schools, particularly those located in Phnom Penh, generally possess better educational facilities, stronger internet connectivity, more qualified teachers, and broader access to learning resources compared to rural schools. Conversely, many rural educational institutions continue to experience infrastructure limitations, shortages of qualified teachers, limited technological access, and socioeconomic barriers that influence students’ educational participation and learning outcomes. The COVID-19 pandemic further intensified these disparities through unequal access to online learning and digital technology. This study aims to explore forms of rural–urban educational inequality in Cambodia, identify factors contributing to unequal learning access, understand the experiences of educational stakeholders regarding educational disparities, and formulate recommendations for equitable educational policies. The study employs a qualitative descriptive approach to examine educational inequality from the perspectives and lived experiences of teachers, students, school principals, and local education officers. Data are collected through semi-structured interviews, observations, and document analysis in selected rural and urban schools. The findings are expected to reveal that educational inequality in Cambodia is strongly influenced by disparities in infrastructure, teacher quality, digital access, and socioeconomic conditions. The study also highlights how geographic location shapes students’ educational opportunities and learning experiences. Furthermore, the research emphasizes the importance of inclusive educational policies, equitable resource allocation, teacher professional development, and digital infrastructure expansion to support equitable learning access. This study contributes to the broader discussion of educational equity and rural educational development in developing countries.